Evaluation of Analgesic Effect of Caudal Epidural Tramadol, Tramadol-Lidocaine, and Lidocaine in Water Buffalo Calves (Bubalus bubalis) - Ayman Atiba; Alaa Ghazy; Naglaa Gomaa; Tarek Kamal; Mustafa Shukry (Veterinary Medicine International)
Aim of this study was to compare the analgesic effect of tramadol and a combination of tramadol-lidocaine with that produced by lidocaine administration in the epidural space in buffalo calves. In a prospective randomized crossover study, ten male buffalo calves were used to compare the epidural analgesic effect of tramadol (1 mg/kg) and tramadol-lidocaine combination (0.5 mg/kg and 0.11 mg/kg, resp.) with that produced by 2% lidocaine (0.22 mg/kg). Loss of sensation was examined by pin-prick test. Onset time, duration, and degree of analgesia and ataxia were recorded after each treatment. Heart rate (HR), respiratory rate (RR), rectal temperature, and haematobiochemical parameters were recorded after all treatments. Time to onset and duration of analgesia, respectively, were as follows: tramadol 11±2 min and 208±15 min; tramadol-lidocaine 6±2 min and 168±9 min; lidocaine 4±1 min and 67±13 min. Onset time and duration were significantly longer with tramadol than the other treatments. Duration was significantly longer with tramadol-lidocaine than lidocaine. Ataxia was mildly observed in tramadol-lidocaine and was moderate in lidocaine. HR, RR, and rectal temperature did not differ significantly from baseline after any treatment. Haematobiochemical parameters returned to basal levels by 24 h after all treatments. This combination might be clinically useful to provide analgesia in buffalo for long-duration surgical procedures.